2022
DOI: 10.3390/vaccines11010092
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Urological Tumors on YouTubeTM: An Information-Quality Analysis

Abstract: Background: YouTubeTM is an open-access source for mass information. Several previous studies of YouTubeTM videos showed a high rate of misinformation in the urological field. The aim of the current study was to evaluate the quality of information on immunotherapy (IMT) for urological tumors uploaded to YouTubeTM. Methods: YouTubeTM videos were searched using nine keyword combinations. The PEMAT, the DISCERN tool, and the Misinformation scale were used to assess the quality of information in YouTubeTM videos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…However, the medical content available on the internet is controversial and has not been properly examined. Di Bello et al [ 9 ] reported that YouTube videos have contributed to the spread of misinformation by underestimating the role of information on immunotherapy for urological tumors in a multimodality approach and missing the findings of published clinical trials. Not only were audiences not availing of accurate therapy, but also they were opting for therapies that may be harmful, which could lead to other complications [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the medical content available on the internet is controversial and has not been properly examined. Di Bello et al [ 9 ] reported that YouTube videos have contributed to the spread of misinformation by underestimating the role of information on immunotherapy for urological tumors in a multimodality approach and missing the findings of published clinical trials. Not only were audiences not availing of accurate therapy, but also they were opting for therapies that may be harmful, which could lead to other complications [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the analysis revealed no relevant differences between the videos dedicated to patients and the content addressed to healthcare workers; therefore, it is plausible that videos on mental health uploaded on YouTube™ are not a useful source of educational content for both the public and healthcare professionals. Furthermore, through an evaluation of the overall scores split by the years in which the videos were uploaded ( Figure 2 ), we observed that following the SARS-CoV-2 pandemic, both the number of videos and the quality or their content were unvaried, even though the global prevention measures adopted to contain the infection had fostered telemedicinal practices to support, educate, and address patients’ needs [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diese Daten belegen die hohen Kosten der Immuntherapie beim PCa [200]. Wir sehen in der Immuntherapie eine große Chance [201]. Allerdings müssen die Kosten dieser Behandlung gegen ihre Wirksamkeit abgewogen werden.…”
Section: Diskussionunclassified